Fragile (X) expression induced by FUdR is transient and inversely related to levels of thymidylate synthase activity. - Cantú, E S (1985)
Thymidylate synthase (TS) activity was monitored in fluorodeoxyuridine (FUdR)-treated lymphoblasts from individuals carrying the fragile (X) [fra(X)] chromosome. Fra(X) expression and levels of TS activity were measured over a 72-hr period at different cell densities. TS activity was 80%-90% inhibited immediately after exposure to FUdR and remained suppressed for the first 24 hrs. Fra(X) expression was not found until 6-8 hrs after FUdR treatment, and at 24 hrs, reached a maximum expression of approximately 50%. At 48 and 72 hrs, however, increasing levels of TS activity paralleled a dramatic drop in fra(X) expression. High fra(X) expression at 48 and 72 hrs could be maintained by rechallenging cultures with increasing doses of FUdR. At low cell densities, fra(X) expression was maintained at high levels for a much longer period of time. In two lymphoblastoid cell lines from obligate carriers, which either expressed at very low levels or did not express the fra(X) in routine cultures, TS activity was also 90% inhibited but with no corresponding fra(X) expression 12 or 24 hrs after FUdR treatment. We conclude that: FUdR inhibits TS activity immediately and induces fra(X) expression 6-8 hrs later, FUdR-induced fra(X) expression and TS activity are inversely related, the FUdR effect on fra(X) expression and TS activity is time and cell-density dependent, and inhibition of TS activity is a necessary but not sufficient condition for fra(X) expression.